The effect of low-dose contraceptive pills on some blood parameters in Iraqi women (Journal of the College of Basic Education, 2022)
This study was carried out in order to investigate the effect of oral contraceptive pills (microgynon) on some physiological and biochemical parameters in Iraqi women for the period from December 2013 to May2014. The study involved 69 apparently healthy women an oral contraceptives (user group) and 26 apparently healthy women not an oral contraceptives (control group). Both groups were aged (18-36 ) years ,all of them were attending AL- Aksa family planning center in Baghdad , Baghdad AL- jadedah. both groups also devided into three groups according to the duration of pills usage: The first group from(3 month -1 year) the second group from(1year-3 years) and the third group from(3 years-5years) Blood sa mples were collected from both groups (user and control) in order to do the following tests: Whole blood picture (Hb, RBCs, PCV, WBCs, and Platelates). The results of current study revealed :There is no statistical significant changes in RBCs ,Hb ,PCV and platelates in user group compared with the control group .but increase apparent after 5 years of using the contraceptive pills .There is a decrease of monocytes but not in the other types of WBCs in user group compared with control group. while observed an increase in monocytes and lymphocytes after 5 years of contraceptive pills.